Peranan Komisi Pemilihan Umum Kota Medan Dalam Memberikan Pendidikan Politik Bagi Penyandang Disabilitas (Studi Kasus Di Kota Medan) - Nizar Nazlia; Heri Kusmanto; Muhammad Aswin Hasibuan; Bahrum Jamil (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2019)
The research is to know the extent to which the role of the General Elections Commission (KPU) the city of Medan in providing political education for persons with disabilities in the city of Medan and what obstacles or barriers of the General Elections Commission (KPU) the city of Medan in providing political education for persons with disabilities in the city of Medan.The method used is the method of qualitative. The results of the researchers is the Electoral Commission of the city of Medan it’s been carrrying out their duties, but is not maximized. The role of the General Elections Commission (the KPU) the city of Medan in providing political education for persons with disabilities in the city of Medan, which is held a discussion with persons with disabilities, making smart  house election, election of access for persons with disabilities, and enhance cooperation with the organization and the persons with disabilities in the city of Medan.The obstacles faced by the General Elections Commission (KPU) the city of Medan in providing political education for persons with disabilities, the constraint of internal Commission is combining between material and methods in the provision of political education, and constraint of exsternal the obstacles in the process of data collection the number of persons with disabilities.From the results of these studies can be picked up the conclusion that the General Elections Commission (KPU) the city of Medan carry out its role in providing political education for persons with disabilities in the city of Medan, though not for a maximum.